CONCENTRATION AND TEMPERATURE DEPENDENCES IN EPR SPECTRA OD GD3+ PROBE CENTERS IN THE Pb1-x AgxS и Pb1-xCuxS (0 ≤ x ≤ 0,011) THERMOELECTRIC CRYSTALS - A. M. Sinicin; R. R. Zainullin; V. A. Ulanov (Известия высших учебных заведений: Проблемы энергетики)
Concentration and temperature dependences of parameters of the EPR spectra of Gd3+ centers introduced into the Pb1-xAgxS and Pb1-xCuxS thermoelectric semiconductor crystals (0 ≤ x ≤ 0,011) were investigated by means of EPR method. The crystals under investigation were grown from the melt containing lead sulfide, silver (or copper) sulfide, gadolinium and sulfur (the latter was used to provide stoichiometry). The investigations were performed in the 9320÷9340 MHz frequency range at temperatures of 4.2, 77, and 300 K. It was established that in the samples studied the silver and copper impurities did not create significant distortions in the structure of the base PbS crystal, but significantly affected the concentration of free carriers. Analysis of the obtained data on the concentration and temperature dependences of the spin-Hamiltonian parameters of the Gd3+ probe centers leads to the conclusion that silver and copper in the PbS crystal are acceptor like impurities, and also to determine their solubility and describe the distortions induced by them in the structure of the base crystal.